Short-term pegylated interferon alpha in chronic HBV patients with ultra-low HBsAg: a retrospective study - Liu, Huimin; Gong, Hongmei; Tan, Zhaoxia; Wu, Yanyan; Ran, Lijian; Mao, Qing; Deng, Guohong; Jiang, Li; Xia, Jie (Frontiers in Cellular and Infection Microbiology, 2025)
Background and aimsHepatitis B surface antigen (HBsAg) clearance—defined as an HBsAg level below the lower limit of detection—is critical for the functional cure of chronic hepatitis B (CHB). This study evaluated the efficacy of short-term pegylated interferon alpha (Peg-IFNα) therapy in achieving HBsAg clearance in CHB patients with ultra-low HBsAg levels (<50 IU/ml).MethodsA total of 378 CHB patients with HBsAg levels <50 IU/ml were enrolled, including 206 nucleos(t)ide analogue (NUC)-treated patients and 172 inactive HBsAg carriers (IHCs). The NUC-treated cohort was divided into 83 patients receiving additional Peg-IFNα treatment (NUC add-on Peg-IFNα group) and 123 patients continuing NUC monotherapy (NUC group). The IHC cohort was divided into 86 patients receiving Peg-IFNα treatment (Peg-IFNα group) and 86 untreated patients (untreated group). The primary endpoint was the HBsAg clearance rate at week 24.ResultsAt week 24, the HBsAg clearance rates in the NUC add-on Peg-IFNα group and Peg-IFNα group were 69.88% and 55.81%, respectively (p = 0.059), both significantly higher than the zero clearance rates in the NUC and untreated groups (p < 0.001). Patients with baseline HBsAg <10 IU/ml achieved higher clearance rates [81.82% vs. 73.81% (p = 0.144)]. A decline of ≥95.8% in HBsAg levels from baseline to week 12 predicted HBsAg clearance at week 24 (AUC ≥0.9, sensitivity 0.765, specificity 0.961).ConclusionsShort-term Peg-IFNα therapy achieved high and comparable HBsAg clearance rates within 24 weeks in NUC-treated patients and IHCs with ultra-low HBsAg levels.Clinical trial registrationhttps://www.medicalresearch.org.cn/login, identifier MR-50-24-011565.